(untitled) (Research, Society and Development, 2021)
The study aimed to raise the theoretical framework through an infometry to identify the state of the art on "Corporate Governance", "Information", "Information technology", "Stock Pricing" and "Market risks", in Portuguese / English, based on keywords / terms, researched in the Web of Science and Scopus databases in the period from 2015 to 2020. For this portfolio, a bibliometric analysis and a systematic review of the literature was carried out in order to build the referent knowledge. to matters. As the articles in the Scopus database were also present in the Web of Science database and because there were a smaller number of articles found in the Scopus database, it was decided to keep only the articles of the Web of Science database, a total of 307 articles, in continuity of research. English; as the base chosen is a very complete, multidisciplinary base and access to the use of the VOSViewer and NVivo software used in this study is acceptable. The articles analyzed were all from 2020 because they are as current as possible. It is inferred that in this study most authors study in isolation, without connections. Document analysis was performed in the bibliographic coupling of 30 articles. Thus, the novelty and gap in the research stands out. It is stated that the words searched for in the study when all together with the Boolean operators are not found in the respective articles. Although in all the articles studied, the term “Information” is only explained. The importance of this term for the authors is well known, in a broad context it is understood that “information” is an essential element for human survival.